Impacts of Covid-19 on households in ASEAN countries and their implications for human capital development: Medium-run impacts and the role of government support - Peter J. Morgan; Long Quang Trinh; Kunhyui Kim (Asian Development Bank Institute (ADBI), 2022)
The outbreak of the COVID-19 virus and the resulting falls in demand due both to uncertainty and policy interventions such as lockdowns, "social distancing," and travel restrictions are having a severe impact on Asian economies and hence on Asian households. These negative impacts come through a variety of channels, including loss of employment or reduced working hours, loss of sales and income of a household business, inability to travel to work, an increased need to stay at home to look after children or sick household members, higher prices and/or lack of availability of staple items, reduced access to schooling, etc. At the same time, governments implemented aid programs to support households and businesses. In order to better understand these impacts, we carried out computer-assisted telephone interviews of households in seven ADB developing member countries: Cambodia, the Lao People's Democratic Republic, Indonesia, Malaysia, the Philippines, Thailand, and Viet Nam. Two waves of the survey were conducted: the first from the end of May to the end of July 2020 and the second from the end of January to February 2021. The following factors contributed to declines in income and expenditure and the experience of financial difficulty: being in a lower-income group, lower education of household head, female household head, having at least one person who lost their job, and being located in a lockdown area. The receipt of government aid did not vary much by income class, but the amount relative to pre-pandemic income was much higher for lower-income groups. Nonetheless, we could not find positive effects of the receipt of government aid on household income or expenditure. One of the most striking findings is that 60% of households experienced financial difficulties during the first-wave period, and this ratio actually increased to 78% in the second-wave period. This suggests that the prolonged nature of the pandemic has put increasing strains on household finances, even though incomes have stabilized somewhat. Only about 7% of children who stopped attending school could not participate in online learning, but some could only participate partially due to weak/insufficient Internet connections and a lack of digital devices. Two COVID-19-related factors-having at least one person who lost their job or had their working hours reduced and experiencing financial difficulties-significantly affect the intensity of online classes taken by children in an average household. This has negative implications for longer-term human capital formation.
Keywords: D14; G51; H12; H84; I10; I24; J6; 330; COVID-19; ASEAN; household income; employment; consumption; household finance; government aid